Implementing augmented reality technology for learning experience enrichment in acquiring Arabic language - Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri; Nordin, Fitri Nurul’Ain (Universiti Sains Islam Malaysia (USIM), 2017)
The aim of this study is to implement how to use Augmented Reality (AR) technology in learning Arabic language. It presents studies from the literature about the best techniques in applying this technology mainly for language learning purposes. The study also enlists related thematic topics and language skills which can be enhanced using augmented reality assistance. A descriptive approach has been applied in reviewing and analysing critically the academic documents and sources. This is followed by a developmental approach where a common model of ADDIE is utilized and accordingly implemented. The study reveals some significant findings in field of the teaching and learning Arabic language. The AR technology not only enhances the students’ language skills, but it contributes positively to favourability and motivation among the learners. The AR based materials also compensate the lack of resources in the related institution. Furthermore, it helps in reducing the cost allocated for the learning as well as teaching processes as the actual content is brought and embedded onto the technology itself. The study encapsulates necessary characteristics in the use of AR for educational purposes form its underlying videos, 3D animations, recorded audios and accompanying data.